2D segmented large inkjet printhead for high speed 3D printers. (7th April 2015) - Einat, Moshe; Bar-Levav, Elkana
Abstract: Three-dimensional (3D) printing is a fast-developing technology these days. However, 3D printing of a model takes many hours. Therefore, the enlargement of the printhead and the increase of the printing speed are important to this technology. In order to enable the enlargement of the printhead a different approach and design are suggested and tested experimentally. The printhead is divided into small segments; each one is autonomous, and not fluid-connected to the neighboring segment. Each segment contains a micro reservoir and few nozzles. The segments are manufactured together in close proximity to each other on the same substrate enabling area coverage. A segmented printhead based on this approach was built and tested. The micro reservoir ink-filling method and operation of the segments were experimentally proven. Ink drops were obtained and the lifetime of the resistors was measured. Electrical characteristics of power and energy for proper operation were obtained. A 3D model printed according to the suggested approach can be completed in less than a minute.